Threshold conditions for sand movement on a rippled bed - Kapdasli, M. S.; Dyer, K. R. (Springer Science and Business Media LLC, 1986)
Flume experiments have been carried out to determine the threshold of grain movement on a rippled bed. The results indicate a form drag component of between 5 and 12 times the skin friction. The threshold of motion on the rippled sand bed can be represented by τ = 70D0.3 in whichD > 0.09 cm.